Approaches for Health Effect Characterization in Risk-Benefit Assessment of Foods: A Comparative Case Study - Thomsen, Sofie Theresa; Nauta, Maarten; Jakobsen, Lea Sletting; Jakobsen, Marianne Uhre; Mejborn, Heddie; Outzen, Malene; Poulsen, Morten; Ravn-Haren, Gitte; Andersen, Rikke (Frontiers in Nutrition, 2021)
One of the challenges in quantitative risk-benefit assessment (RBA) of foods is the choice of approach for health effect characterization to estimate the health impact of dietary changes. The purpose of health effect characterization is to describe an association between intake of a food or food component and a health effect in terms of a dose-response relationship We assessed the impact of the choice of approach for health effect characterization in RBA in two case studies based on substitution of i) white rice by brown rice and ii) unprocessed red meat by vegetables. We explored this by comparing the dose-response relations linking a health effect with i) a food component present in the food, ii) a food based on non-specified substitution analyses, and iii) a food based on specified substitution analyses. We found that the choice of approach for health effect characterization in RBA may largely impact the results of the health impact estimates. Conducting the calculations only for a food component may neglect potential effects of the food matrix and of the whole food on the diet-disease association. Furthermore, calculations based on associations for non-specified substitutions include underlying food substitutions without specifying these. Data on relevant specified substitutions, which could reduce this type of bias, are unfortunately rarely available. Assumptions and limitations of the health effect characterization approaches taken in RBA should be documented and discussed, and scenario analysis is encouraged when multiple options are available.